ChemInform Abstract: Enantioselective Strecker Reaction of Aldimines Using Potassium Cyanide Catalyzed by a Recyclable Macrocyclic V(v) Salen Complex. Issue 15 (24th March 2016) - Saravanan, S.; Khan, Noor‐ul H.; Jakhar, Ajay; Ansari, Amamudin; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Kumar, Gaurav
Abstract: The title reaction affords α‐aminonitriles in good yields with high enantioselectivities.